A modified pump-down model for high vacuum packaging of vacuum insulation sandwiches under readsorption effect. (May 2023) - Mei, Zhengwei; Bi, Hailin; Cao, Qing; Lin, Wenyu; Wu, Binxing; Wang, Xudi
Abstract: Thermal insulation performance and service life of vacuum insulation sandwiches depend significantly on the internal residual gas pressure. Degradation of the vacuum can lead to a dramatic increase in thermal conductivity, so the initial internal pressure should be kept as low as possible during fabrication. In this paper, the evacuation and outgassing of vacuum insulation sandwiches are studied by modeling and experimental methods. A modified pump-down model for vacuum insulation sandwiches, called the recombination-dissociation-limited model, is proposed based on diffusion, recombination, and dissociation. The results show that the recombination and the dissociation of hydrogen on the inner surface have a hysteresis effect on the evacuation process, which explains well that the pressure inside the device remains above the ultimate pressure of the vacuum system after packaging. The experimentally measured evolution of the pressure and outgassing rate in the vacuum insulation sandwiches agree well with the calculated results. The simulation analyses the effects of temperature, pump-out port size, and ultimate pressure on evacuation efficiency. It provides a theoretical basis for predicting the dynamic pressure evolution during high vacuum packaging and selecting effective parameters in the packaging process. Highlights: A modified pump-down model for vacuum insulation sandwiches is proposed. Hysteresis mechanism of high vacuum packaging processes under readsorption effect. Prediction of the dynamic evolution of pressure in high vacuum packaging processes. Methods for improving the efficiency of high vacuum packaging.